Antitumor Effect of Zerumbone Isolated from Lempoyang (Zingiber Zerumbet) on Human Cervical Cancer Cells and Mouse Cervical Intraepithelial Neoplasia - Abdelwahab, Siddig Ibrahim (2009)
Malaysia as a tropical country is a rich source of biologically active phytochemicals, which could be useful as an alternative to the current unsafe regimens of cancer treatment. This includes the use of cisplatin (CIS), the current chemotherapeutic drug to treat cervical cancer, the second most lethal cancer affecting women in Malaysia. Therefore, anti-tumor activities of zerumbone (ZER) were investigated in both in vitro and in vivo cervical cancer models. This natural compound was isolated from the edible plant Zingiber zerumbet, locally known as Lempoyang, through column chromatography and hydrodistillation methods. The chemical structure of ZER was confirmed using NMR. The cytotoxic effects of ZER were tested in human cervical cancer cell lines (HeLa) using MTT assay and compared concurrently to cisplatin. Zerumbone’s induction of HeLa cancer cell deaths were quantified using AO/PI double staining and flow cytometry. Transmission and scanning electron microscopic analyses were done to evaluate ultra-morphological changes. The effect of ZER on caspase-3 and caspase-9 was evaluated colorimetrically in HeLa cells. The in vivo model of cervical intraepithelial neoplasia (CIN) was induced in pregnant female Balb/c mice using Diethylstilboestrol (DES). Cervical tissues were stained with hematoxylin and eosin (H&E) and viewed under light microscopy and the in vivo antiproliferative properties of ZER was confirmed by the immunohistochemical staining of proliferating cellular nuclear antigen (PCNA) as a proliferation marker and the PCNA labeling index was obtained. Apoptosis (Bcl-2 & Bax) and G2/M-cell cycle arrest (cdc25B, cyclinB1 and Chk2) associated proteins were investigated using immunohistochemistry. Moreover, RT-PCR was used to amplify mRNA of Bcl-2, Bax, c-myc and β-actin genes. The genetic material was obtained by laser capture microdissection microscopy (LCMM). No previous toxicological investigations have been carried out on this compound. Hence, acute, sub-acute and sub-chronic toxicity studies and ZER was evaluated for its behavioural, biochemical and histo-pathological effects. Findings of NMR coincide to the previously published data. However, ZER was able to exert an antiproliferative effect towards HeLa when isolated by both hydrodistillation and column chromatography, with an IC50 of 20.30±1.1 μM and 20.41±0.9 μM (p>0.05, student t-test, n=3), respectively. AO/PI-stained HeLa cells showed that ZER induced apoptosis in a time-dependent manner with insignificant statistical (p>0.05) difference in necrosis between various doses of this compound. Moreover, flow cytometric evaluation of the effect of ZER on DNA content by cell cycle phase distribution revealed that the cell populations at G0 and G2/M phases were significantly different (p<0.05) as compared to the untreated population. Antitumour activities of ZER were further confirmed by transmission and scanning electron microscopy investigations, which showed distinctive morphological changes corresponding to metaphasal arrest and the typical apoptosis. The colorimetric assay of caspase-3 and caspase-9 revealed a statistical significant difference between treated and untreated cells. In vivo model results disclosed that ZER (16 mg/kg) has the capability to regress significantly (p<0.05, χ2 statistics) the proliferation of cervical intraepithelial neoplasia (CIN) from CIN3 to CIN1 resembling the anti-tumor effects of CIS 10mg/kg. Moreover, this antiproliferative property was further confirmed by the regression of the PCNA, an in vivo proliferation marker, which showed also a dose-dependent (p<0.05) effect of ZER on the PCNA labeling index (PCNA positive nuclei). It has been found that ZER also modulated the ratio of Bcl-2 and Bax, which further supported the intonated levels of LCMM extracted and RT-PCR amplified mRNA of such proteins as well as c-myc oncogene, which was detected only in the CIN cancer group. Cervical tissues from female Balb/c mice treated with 16mg/kg of ZER, showed decreased levels of CyclinB1 and cdc25B immunoreactivity and associated with upregulation of Chk2 immunoexpression. Acute and subacute administration of ZER did not cause abnormalities on body weight, liver morphology or serum AST concentration. Moreover, sub-chronic study showed ZER did not modify significantly (p>0.05) serum concentrations of AST, ALP, ALT and GGT. No histopathological changes were observed in the hepatic, renal, cardiac and gastrointestinal tissues. These histomorphological findings were supported by the insignificant differences (p>0.05) between the mean lesion scores of hepatic and renal tissues. Collectively, results presented in this study demonstrated that ZER causes metaphasal blockage in HeLa cells, leading to growth inhibition and apoptosis, which was later confirmed to be through mitochondrial pathways. As ZER exhibits similar pharmacological activity to CIS, it possesses the potential to be developed as an antiproliferative agent for cervical cancer but producing less side effects, as the compound was shown to have no toxicological signs compared to the clinical complications of CIS.